Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fphar.2022.870407
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Gut Microbiota and Metabolites by Berberine in Treating Mice With Disturbances in Glucose and Lipid Metabolism

Abstract: Introduction: Glucose and lipid metabolism disturbances has become the third major disease after cancer and cardio-cerebrovascular diseases. Emerging evidence shows that berberine can effectively intervene glucose and lipid metabolism disturbances, but the underlying mechanisms of this remain unclear. To investigate this issue, we performed metagenomic and metabolomic analysis in a group of normal mice (the NC group), mice with disturbances in glucose and lipid metabolism (the MC group) and mice with disturban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…However, the abundance of another 21 species of bacteria (such as Bifidobacterium animalis, Bacillus velezensis, Lachnospiraceae bacterium_M18-1, Eubacterium sp_14-2, and Helicobacter ganmani) was significantly reduced. Interestingly, arbutin was reported to reduce colitis symptoms and inhibit lipopolysaccharide-induced inflammation (41), and there were significant negative correlations between arbutin contents and the enriched gut microbiota (e.g., Eubacterium and Ruminococcus) (42), suggesting that there was bactericidal ability about arbutin.…”
Section: Discussionmentioning
confidence: 99%
“…However, the abundance of another 21 species of bacteria (such as Bifidobacterium animalis, Bacillus velezensis, Lachnospiraceae bacterium_M18-1, Eubacterium sp_14-2, and Helicobacter ganmani) was significantly reduced. Interestingly, arbutin was reported to reduce colitis symptoms and inhibit lipopolysaccharide-induced inflammation (41), and there were significant negative correlations between arbutin contents and the enriched gut microbiota (e.g., Eubacterium and Ruminococcus) (42), suggesting that there was bactericidal ability about arbutin.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolites of the gut microbiota such as secondary bile acids, TMAO and LPS have also been reported to be involved in host lipid metabolism. 47,48 The PICRUSt predicted results showed that GBR supply improved energy metabolism, lipid metabolism, glycolysis and gluconeogenesis, which were closely related to metabolism (Fig. S3 †).…”
Section: Food and Function Papermentioning
confidence: 97%
“…BBR interacts with intestinal microorganisms to derive a variety of metabolites, such as short-chain fatty acids (SCFAs), trimethylamine-N-oxide (TMAO), and branched-chain amino acids (BCAAs) ( Fang et al, 2022 ). These derivatives and the signaling pathways they influence have a large impact on lipid levels and, as such, may be used to treat lipid metabolic diseases.…”
Section: The Role Of Bbr In Regulating Lipid Metabolism In the Intestinementioning
confidence: 99%